2015
DOI: 10.1007/s13355-015-0359-2
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of microsatellite markers for the fruit fly, Bactrocera tau (Diptera: Tephritidae)

Abstract: to the oriental fruit fly, Bactrocera dorsalis (Hendel) (Wan et al. 2011), which limits the development of agriculture in many countries due to reduction in farm income; it also leads to overuse of pesticides. The difficult problems in B. tau control are to rapidly and accurately identify the morphologically similar cryptic species complexes, and reconstruct historical processes to tackle the issue of the origin and range expansion (Dujardin and Kitthawee 2013). Microsatellites, also known as simple sequence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…We found the lowest H O value at locus Tin06 (0.05-T. incompleta) and the highest value at loci Tbi02 for T. bicolor and Tgr06 for T. grandis (H E = 0.88). The number of alleles found for Tomoplagia species is consistent with those found in some other species of Tephritidae, such as Anastrepha fraterculus (7-18 alleles per locus, mean = 12.9; Manni et al 2015) and Ceratitis capitata (8-22 alleles per locus, mean = 13.6; Bonizzoni et al 2000), but exceed those found for Anastrepha suspensa (2-12 alleles per locus, mean = 6.1; Fritz and Schable 2004) and Bactrocera tau (2-9 alleles per locus, mean = 4.5; Yan et al 2015). Yan et al (2015) also found a locus with low observed heterozygosity for Bactrocera tau (H O = 0.069), as we found in T. incompleta (locus Tin06).…”
Section: Discussionsupporting
confidence: 88%
“…We found the lowest H O value at locus Tin06 (0.05-T. incompleta) and the highest value at loci Tbi02 for T. bicolor and Tgr06 for T. grandis (H E = 0.88). The number of alleles found for Tomoplagia species is consistent with those found in some other species of Tephritidae, such as Anastrepha fraterculus (7-18 alleles per locus, mean = 12.9; Manni et al 2015) and Ceratitis capitata (8-22 alleles per locus, mean = 13.6; Bonizzoni et al 2000), but exceed those found for Anastrepha suspensa (2-12 alleles per locus, mean = 6.1; Fritz and Schable 2004) and Bactrocera tau (2-9 alleles per locus, mean = 4.5; Yan et al 2015). Yan et al (2015) also found a locus with low observed heterozygosity for Bactrocera tau (H O = 0.069), as we found in T. incompleta (locus Tin06).…”
Section: Discussionsupporting
confidence: 88%
“…However, neither the new (SUW) nor the old (e.g., WYS and WOL) populations are in HWE (Table 1). In fact, due to a heterozygote deficiency, many populations of expansive species are not found to indicate HWE, e.g., among Lepidoptera (Wei et al 2013), Coleoptera (Wu et al 2016) and Diptera (Yan et al 2015). In the case of spiders, HWE has usually been noted in stable-range populations (Ramirez & Chi 2004;Ramirez et al 2007Ramirez et al , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite markers have been developed and used for many fruit fly species (Augustinos et al 2008;Bonizzoni et al 2001;Buahom et al 2013;Leal et al 2021;Lin et al 2020;Qin et al 2018;Wang et al 2021;Yan et al 2015).…”
Section: Introductionmentioning
confidence: 99%